PENGARUH KARAKTERISTIK PEKERJAAN, KEPUASAN KERJA DAN KOMITMEN TERHADAP ORGANISAZIONAL CITIZENSHIP BEHAVIOUR (OCB) KARYAWAN PERUSAHAAN DAERAH AIR MINUM (PDAM) KOTA MALANG - Saras Anjarwati; Hadi Sunaryo; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThis study aims to determine the effect of job characteristics, job satisfaction and commitment to the Organizational Citizenship Behavior (OCB) of PDAM Malang employees. The sample and population in this study amounted to 44 people who were employees of the Regional Water Supply Company (PDAM) in Malang City.The method used is descriptive data analysis, namely by using tests of validity, reliability, normality, multicollinearity test, heterokesdasticity test, multiple linear analysis test, f test, and hypothesis test t.The results of this study indicate that simultaneously each variable job characteristics, job satisfaction, and commitment both have a positive effect on Organizational Citizenship Behavior (OCB, while partially the job characteristics variable has an effect on Organizational Citizenship Behavior (OCB), the job satisfaction variable is not has an effect on the Organizational Citizenship Behavior (OCB), and commitment does not affect the Organizational Citizenship Behavior (OCB) in the Regional Water Company (PDAM) of Malang City. Keywords : Job characteristics, job satisfaction, commitment and Organizational Citizenship Behavior (OCB)